Policing suicide: investigative officers’ views on criminalisation and enforcement of anti-suicide laws - Aborisade, Richard Abayomi (Policing and society, 2023)
The global calls for the decriminalisation of suicide have been intense, leading to several countries repealing laws against suicide and suicidal behaviour. However, this opened up a gap in knowledge on suicide policing in countries that maintained statutes penalising suicide. Drawing from the case of Nigeria, one of the countries where attempted suicide attracts prison sentences, this study explored the opinions and experiences of police officers as regards the criminalisation of suicide and enforcement of anti-suicide laws. Sixty-four (64) suicide investigating police officers in six zonal commands of the Nigeria Police Force were engaged in a qualitative study under an interpretative paradigm. Participants reported negative perceptions of anti-suicide laws and policing of suicide through communities’ display of lack of belief, low level of trust, lukewarm or negative attitudes, uncooperative postures, and low level of support. The study sample held that the anti-suicide laws are not effective in the country as evidenced by the low rate of apprehensions and convictions, despite increasing figures of suicide mortality. The study findings highlighted the need for the Nigerian government to consider the decriminalisation of attempted suicide and be more responsive to socioeconomic factors driving the increase in suicide in the country.